Effect of basal and foliar application of boron and zinc on yield attributes in Solanum melongena L. - Chauhan, S. V. S.; Rana, A.; Chauhan, S. (International Journal of Horticultural Science, 2004)
Field experiments were conducted during 1999-2000 and 2000-2001 to study the effect of basal application (BA) of zinc sulphate (5 and 10 mg kg-i soil) or boric acid (1 and 2 mg kg-1 soil) alone or foliar applications (FA) of water or 1% ZnSO4 or 1% H3 B03 or the combinations of both BA and FA of either ZnSO4 or H3 B03 on yield attributes (number of flowers and fruits/ plant, fruit weight, size and total yield). On the basis of the two-year data, it was found that all the treatments of BA as well as FA enhanced yield attributes but the combination of BA of 10 mg kg--1 soil ZnSO4 and FA of 1% H3 B03 gave highest yield as compared to other treatments and control plants.